STUDI REAKTOR PLASMA DIELECTRIC BARRIER DISCHARGE (DBD) PLANAR TO PLANAR UNTUK PRE-TREATMENT KONVERSI LIMBAH PLASTIK POLIPROPILEN MENJADI BAHAN BAKAR CAIR - Aniyati Khoiriyah; M.C.T. Wahyu Utami; I. Istadi (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Polipropilen (PP) is a kind of plastic that is widely used in our life. Plastic wastes give big problems to environment because plastic wastes are not easily degraded by nature. Conventional method for plastic waste processing is thermal cracking and catalytic cracking. The conventional process needs high energy. Plasma technology combined with catalytic cracking process is expected to cover the problems of energy requirement. Distance between both electrodes (high voltage and ground) and high voltage magnitude in plasma reactor is important parameter in plasma reactor operation and type or design of plasma reactor. Optimum of both important parameters need to be studied in order to get optimal operating condition suitable for better productivity. DBD Planar to Planar plasma reactor can be used to pre-crack polipropilen's structure (in the pre-treatment's process) so that catalytic cracking process in fixed bed's reactor conventional that use RCC (Residual Catalytic Cracking) catalyst can be easier to take. On this plasma reactor, distance between both electrodes of 2,5 - 4 cm, and the high voltage of 3-7,5 kV are optimal operating conditions. Combination of the pre-treatment (distance between electrodes 3,3 cm and high voltage 5,3 kV) and the conventional catalytic cracking process by using weight ratio of catalyst to plastic 2:1 and reactor temperature 500oC and reaction time 1 hour could produce liquid fuel yield of 36,27%.